Detection of Low-Frequency KRAS Mutations in cfDNA From EGFR-Mutated NSCLC Patients After First-Line EGFR Tyrosine Kinase Inhibitors - Nardo, Giorgia; Carlet, Jessica; Marra, Ludovica; Bonanno, Laura; Boscolo, Alice; Dal Maso, Alessandro; Boscolo Bragadin, Andrea; Indraccolo, Stefano; Zulato, Elisabetta (Frontiers in Oncology, 2021)
Background: Molecular profiling of advanced EGFR mutated NSCLC has recently demonstrated the co-existence of multiple genetic alterations. Specifically, co-existing KRAS-mutations in EGFR NSCLCs have been described, despite their prevalence at progression and their role in the response to EGFR tyrosine kinase inhibitors (TKIs) remain marginally explored. Aim of our study was to investigate the prevalence of co-existing KRAS mutations at the time of progressive disease and explore their impact on clinical outcome. Materials and methods: We retrospectively analysed by digital droplet PCR prevalence of KRAS co-mutations in 106 plasma samples of EGFR mutated NSCLC patients, in progressive disease after EGFR TKI treatment as first-line therapy. Results: KRAS co-mutations (codon 12 and 13) were identified in 3 patients (2.8% of analysed samples), with low allelic frequency (<0.2%), and had a negative impact on clinical outcome to first-line EGFR TKI. Conclusion: Detection of KRAS mutations in cell-free DNA of EGFR mutant NSCLC patients at progression after first or second generation EGFR TKI is a rare event. Due to their low abundance, the negative impact of KRAS mutations on the response to EGFR TKI remains to be confirmed in larger studies.